Prices, Money Supply and Output Nexus in Pakistan – A Macro Econometric Model - Awan, Asma; Ahmad, Hafiz Khalil; Hussain, Altaf; Marri, Muhammad Yousuf Khan (iRASD Journal of Economics, 2021)
This study is an endeavor to examine joint determination of prices, money supply and output in Pakistan during 1975-2019 by using macro-economic model and annual time series data. Three Stage Least Square (3SLS) method is utilized to estimate simultaneous model of prices, money supply and output nexus. Our results strongly support significant positive association between prices and money supply thus supports monetarist view that growth in money supply causes inflation and rising behavior of prices is detrimental to real output. The accelerated inflation has obstructed real output and reduced output levels has further caused jump in price levels during the investigated period. The empirical results also supports significant bi-directional relationship between prices and money supply. Prudent monetary policy is need of hour to stabilize prices in order to minimize its adverse impacts on real output.